PROCESS FOR PRODUCING /E/ -5-/2-BROMOVINYL/-2-COMMA ABOVE-DEOXYURIDINE AND O-ACYL DERIVATIVES - RATONYI,ZOLTAN,HU; VOEROESHAZY,LAJOS,HU; BAERWOLF,DIETER,DD; JUST,HELLMUT,DD; REEFSCHLAEGER,JUERGEN,DD; MRS TUEDOES,FERENCNE,HU; GAL,TIBOR,HU; MRS SZABOLCS,OTTONE,HU; OETVOES,LASZLO,HU; SAGI,JSOS,HU; DAROCZY,IVAN,HU (1986)
(E)-5-(2-bromovinyl)-2'- deoxyuridine and its derivatives of general formula VI (where R is H or as defined below) are prepared from 3,5'-di-O-acyl-5-ethyl- 2'-deoxyuridines of general formula IV (wherein R is C1-8 alkanoyl, benzoyl or benzoyl group substituted in para position by C1-4 alkyl or halogen) by reaction with bromine to give a dibromo derivative of general formula V which is then dehydrohalogenated and if desired deacylated to give the compound of formula of formula (VI) in which R is H. The compounds of formula (VI) in which R is other than H are new compounds and are metabolic precursors for (E)-5-(2-bromovinyl-2'- deoxyuridine. These compounds are thus useful in medicine.